Nosocomial infections and resistance microbian in Intensive Care Unit of a University Hospital - an epidemiological study - Adriana C. Oliveira; Wanessa T. Clemente; Thabata C. Lucas; Glaucia H. Martinho (Online Brazilian Journal of Nursing, 2006)
In the last decades it has been observed an increase in frequency on nosocomial infections by resistant microorganisms, especially in Intensive Care Units (ICU). This study aimed to determine main sites of nosocomial infections and prevalence of multidrug resistant microorganisms. An epidemiological and descriptive study was developed in an adult ICU of a University Hospital of Belo Horizonte, Minas Gerais, from January to December, 2004. Among the most prevalent nosocomial infections were pneumonia, urinary tract infections, and bloodstream infections. Among the resistant microorganisms prevailed Pseudomonas aeruginosa, Acinetobacter baumanii, MRSA, Klebsiella, Enterobacteriaceas and Serratia. As this study is still going on, we expect to determine temporal trends for resistant microorganisms related to nosocomial infections main sites.